ANALISIS PERLAKUAN AKUNTANSI AKTIVA TETAP PADA JNT EXPRESS TANGGETADA - Randi, Randi; Triani, Neks; Bustang, Bustang (Komunitas Manajemen Kompetitif, 2025)
The research uses a descriptive qualitative approach, with data collection techniques including interviews, direct observation, and documentation.The main focus of this research covers the recognition, measurement, depreciation, derecognition, as well as the presentation and disclosure of fixed assets.The results of the study indicate that the recognition and measurement of fixed assets have been carried out in accordance with the provisions of PSAK 216, namely recognized when the assets are ready for use and measured based on acquisition cost. However, discrepancies were found in the depreciation treatment, where the company charged depreciation in full without considering the actual usage period of the assets, and has not yet derecognized assets that are already damaged. In addition, the presentation and disclosure of fixed assets have not been formally implemented in the financial statements. This study recommends the need for a more structured accounting system, proportional depreciation recording, and comprehensive fixed asset disclosure to ensure that financial statements are more reliable, relevant, and compliant with standards. Keywords: Fixed Assets, PSAK 216, Accounting, Depreciation, Recognition